Respostas

  • Usuário do Brainly
2014-02-17T21:18:38-03:00
∆ = b^2 -4.a.c
∆= (-2)^2 -4.1.-3
∆= 4+12
∆=16

x= -b ±√∆ sobre 2a
x= -(-2) ±√16 / 2.1
x= 2 ± 4 / 2

x1= 2-4 / 2 = -1
x2= 2+4 / 2 = 3
A melhor resposta!
2014-02-17T21:22:27-03:00
X² - 2x - 3 ~> a = 1 , b = -2 , c = -3

Δ = b² - 4ac
Δ = (-2)² - 4.1.(-3)
Δ = 4 - (-12)
Δ = 16

x = -b ± √Δ
         2a

x = -(-2) ± √16
          2.1

x = ± 4
       2

x' = 2 + 4 = 6 = 3            x" = 2 - 4 =-2 = -1
        2       2                           2      2

S = { -1 ; 3 }

2 5 2